Business and politics in Europe, 1900-1970 : (Cambridge University Press, 2003)
Providing fresh insights into the interaction between politics and business in twentieth-century Europe, this book indicates the complexity of the relationship--particularly in the environment of the 1920s and 1930s--when fascism was at its height. Distinctive contributions are also made regarding the contrasting behaviors of businessmen and institutions in response to the Great Depression; the rise of Hitler and the "Jewish question"; the role of business networks in the politics of Belgium and Greece; and the business-politics dimension in the formation of the Irish Republic.